SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The influence of an environmentally relevant polychlorinated biphenyl mixture on the intestinal microbiota in post-weaning mouse dams - Hui Wang; Laura E. Dean; Xueshu Li; Rachel L. Fitzjerrells; Kai Wang; Ashutosh K. Mangalam; Rachel F. Marek; Conner L. Kennedy; Monica M. Ridlon; Audrey Spiegelhoff; Kimberly P. Keil Stietz; Hans-Joachim Lehmler (Environmental Science and Pollution Research, 2026)
Polychlorinated biphenyls (PCBs) are environmental pollutants linked to neurological impairments by mechanisms involving the gut microbiome. This study examines the effects of maternal exposure to a PCB mixture on the gut microbiome of post-weaning mouse dams. Female C57BL/6 J mice were exposed daily to PCBs at different doses (0, 0.1, 1, or 6 mg/kg body weight/day) before mating, and throughout gestation and lactation. Post-weaning intestinal contents from dams were analyzed to assess microbiome abundance and quantify PCBs and their metabolites. PCB exposure affected the composition of microbial taxa, though not significantly. However, topic modeling analysis identified a distinct microbial community that was significantly more prevalent in the control group compared to post-weaning mouse dams exposed to the MARBLES mixture at medium and high doses. Complex PCBs and metabolite mixtures were detected in the intestinal contents. Certain PCBs and their metabolites were associated with changes in bacterial abundance, as determined by network analysis. These findings show that individual PCBs and their metabolites can affect gut microbial communities, potentially contributing to neurological impairments in mice exposed to PCBs during gestation and lactation. Graphical Abstract

Maximizing biological insights from instruments attached to animals - Roxanne S. Beltran; A. Marm Kilpatrick; Simona Picardi; Briana Abrahms; Gabriel M. Barrile; William K. Oestreich; Justine A. Smith; Max F. Czapanskiy; Arina B. Favilla; Ryan R. Reisinger; Jessica M. Kendall-Bar; Allison R. Payne; et al. (Trends in Ecology & Evolution, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Ex vivo and in vitro methods as a platform for studying anthropogenic effects on marine mammals: four challenges and how to meet them - Juan Manuel Vazquez; Jane I. Khudyakov; Carla B. Madelaire; Céline A. Godard-Codding; Heli Routti; Emily K. Lam; Elizabeth R. Piotrowski; Greg B. Merrill; Jillian H. Wisse; Kaitlin N. Allen; Justin Conner; Pierre Blévin; et al. (Frontiers in Marine Science, 2024)
Marine mammals are integral to global biodiversity and marine health through their roles in coastal, benthic, and pelagic ecosystems. Marine mammals face escalating threats from climate change, pollution, and human activities, which perturb their oceanic environment. The diverse biology and extreme adaptations evolved by marine mammals make them important study subjects for understanding anthropogenic pressures on marine ecosystems. However, ethical and logistical constraints restrict the tractability of experimental research with live marine mammals. Additionally, studies on the effects of changing ocean environments are further complicated by intricate gene-environment interactions across populations and species. These obstacles can be overcome with a comprehensive strategy that involves a systems-level approach integrating genotype to phenotype using rigorously defined experimental conditions in vitro and ex vivo . A thorough analysis of the interactions between the genetics of marine mammals and their exposure to anthropogenic pressures will enable robust predictions about how global environmental changes will affect their health and populations. In this perspective, we discuss four challenges of implementing such non-invasive approaches across scientific fields and international borders: 1) practical and ethical limitations of in vivo experimentation with marine mammals, 2) accessibility to relevant tissue samples and cell cultures; 3) open access to harmonized methods and datasets and 4) ethical and equitable research practices. Successful implementation of the proposed approach has the potential impact to inspire new solutions and strategies for marine conservation.

Constraining sulfur incorporation in calcite using inorganic precipitation experiments - Szabina Karancz; Joji Uchikawa; Lennart J. de Nooijer; Mariëtte Wolthers; Kyle A. Conner; Corinne G. Hite; Richard E. Zeebe; Shiv K. Sharma; Gert-Jan Reichart (Geochimica et Cosmochimica Acta, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

151 Development and refinement of online horse judging resources: A mixed-methods study - B.L. Parrish; N. Conner; C.M. Brady; K. Hiney; K.P. Anderson (Journal of Equine Veterinary Science, 2023)

145 4-H does more than show to grow: Rebuilding educational opportunities and emphasizing positive youth development in a previously show-only focused program - K. Irvine; C. Wickens; A. Schortinghouse; S. Conner (Journal of Equine Veterinary Science, 2023)

Unpacking the Role of Extracellular Vesicles in Ischemic and Hemorrhagic Stroke: Pathophysiology and Therapeutic Implications - Yonatan Hirsch; Joseph R. Geraghty; Cory R. Reiter; Eitan A. Katz; Conner F. Little; Matthew K. Tobin; Fernando D. Testai (Translational Stroke Research, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Are we ready to track climate‐driven shifts in marine species across international boundaries? ‐ A global survey of scientific bottom trawl data - Aurore A. Maureaud; Romain Frelat; Laurène Pécuchet; Nancy Shackell; Bastien Mérigot; Malin L. Pinsky; Kofi Amador; Sean C. Anderson; Alexander Arkhipkin; Arnaud Auber; Iça Barri; Richard J. Bell; et al. (Global Change Biology, 2021)
Marine biota are redistributing at a rapid pace in response to climate change and shifting seascapes. While changes in fish populations and community structure threaten the sustainability of fisheries, our capacity to adapt by tracking and projecting marine species remains a challenge due to data discontinuities in biological observations, lack of data availability, and mismatch between data and real species distributions. To assess the extent of this challenge, we review the global status and accessibility of ongoing scientific bottom trawl surveys. In total, we gathered metadata for 283,925 samples from 95 surveys conducted regularly from 2001 to 2019. We identified that 59% of the metadata collected are not publicly available, highlighting that the availability of data is the most important challenge to assess species redistributions under global climate change. Given that the primary purpose of surveys is to provide independent data to inform stock assessment of commercially important populations, we further highlight that single surveys do not cover the full range of the main commercial demersal fish species. An average of 18 surveys is needed to cover at least 50% of species ranges, demonstrating the importance of combining multiple surveys to evaluate species range shifts. We assess the potential for combining surveys to track transboundary species redistributions and show that differences in sampling schemes and inconsistency in sampling can be overcome with spatio‐temporal modeling to follow species density redistributions. In light of our global assessment, we establish a framework for improving the management and conservation of transboundary and migrating marine demersal species. We provide directions to improve data availability and encourage countries to share survey data, to assess species vulnerabilities, and to support management adaptation in a time of climate‐driven ocean changes.

Sequencing of Tuta absoluta genome to develop SNP genotyping assays for species identification - Christine A. Tabuloc; Kyle M. Lewald; William R. Conner; Yoosook Lee; Ernest K. Lee; Alexander B. Cain; Kristine E. Godfrey; Judit Arnó; Nuria Agustí; Clerison R. Perini; Jerson C. Guedes; Frank G. Zalom; et al. (Journal of Pest Science, 2019)

Pre-Mating Reproductive Isolation in Tiger Beetles (Carabidae: Cicindelinae): an Examination of the Role of Visual and Morphological Feedback - Te K. Jones; William E. Conner (Journal of Insect Behavior, 2018)

Quantifying nonadditive selection caused by indirect ecological effects: Reply - Casey P. terHorst; Jennifer A. Lau; Jeffrey K. Conner (Ecology, 2017)

Quantifying nonadditive selection caused by indirect ecological effects - Casey P. terHorst; Jennifer A. Lau; Idelle A. Cooper; Kane R. Keller; Raffica J. La Rosa; Anne M. Royer; Elizabeth H. Schultheis; Tomomi Suwa; Jeffrey K. Conner (Ecology, 2015)
In natural biological communities, species interact with many other species. Multiple species interactions can lead to indirect ecological effects that have important fitness consequences and can cause nonadditive patterns of natural selection. Given that indirect ecological effects are common in nature, nonadditive selection may also be quite common. As a result, quantifying nonadditive selection resulting from indirect ecological effects may be critical for understanding adaptation in natural communities composed of many interacting species. We describe how to quantify the relative strength of nonadditive selection resulting from indirect ecological effects compared to the strength of pairwise selection. We develop a clear method for testing for nonadditive selection caused by indirect ecological effects and consider how it might affect adaptation in multispecies communities. We use two case studies to illustrate how our method can be applied to empirical data sets. Our results suggest that nonadditive selection caused by indirect ecological effects may be common in nature. Our hope is that trait‐based approaches, combined with multifactorial experiments, will result in more estimates of nonadditive selection that reveal the relative importance of indirect ecological effects for evolution in a community context.

Southern toads alter their behavior in response to red-imported fire ants - Andrea K. Long; Daniel D. Knapp; Lauren Mccullough; Lora L. Smith; L. Mike Conner; Robert A. Mccleery (Biological Invasions, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

Value Driven Innovation in Medical Device Design: A Process for Balancing Stakeholder Voices - F. J. de Ana; K. A. Umstead; G. J. Phillips; C. P. Conner (Annals of Biomedical Engineering, 2013)

Common Reasons for “For-Cause” Inspections in Bioequivalence Studies Submitted to the Food and Drug Administration - Bing V. Li; Barbara M. Davit; Christina H. Lee; Santhosh K. Pabba; Chitra Mahadevan; Hoainhon T. Caramenico; Sam H Haidar; Aida L. Sanchez; Aaron W. Sigler; Ethan M. Stier; Dale P. Conner (The AAPS Journal, 2013)

Statistics on BCS Classification of Generic Drug Products Approved Between 2000 and 2011 in the USA - Anil K. Nair; Om Anand; Nam Chun; Dale P. Conner; Mehul U. Mehta; Duong T. Nhu; James E. Polli; Lawrence X. Yu; Barbara M. Davit (The AAPS Journal, 2012)

Effects of prescribed fire, supplemental feeding, and mammalian predator exclusion on hispid cotton rat populations - Gail Morris; Jeffrey A. Hostetler; L. Mike Conner; Madan K. Oli (Oecologia, 2011)

Challenges and Opportunities in Establishing Scientific and Regulatory Standards for Assuring Therapeutic Equivalence of Modified Release Products: Workshop Summary Report - Mei-Ling Chen; Vinod P. Shah; Derek Ganes; Kamal K. Midha; James Caro; Prabu Nambiar; Mario L. Rocci; Avinash G. Thombre; Bertil Abrahamsson; Dale Conner; Barbara Davit; Paul Fackler; et al. (The AAPS Journal, 2010)

Intragenic vectors for gene transfer without foreign DNA - Anthony J. Conner; Philippa J. Barrell; Samantha J. Baldwin; Annemarie S. Lokerse; Pauline A. Cooper; Astrid K. Erasmuson; Jan-Peter Nap; Jeanne M. E. Jacobs (Euphytica, 2007)

Assessment of yield loss caused by mycosphaerella blight in field pea crops in western Canada - H. Su; S. F. Hwang; K. F. Chang; R. L. Conner; A. G. Xue; T. D. Warkentin; S. F. Blade; G. D. Turnbull (Journal of Plant Diseases and Protection, 2006)

Characterizing ecological generalization in plant-pollination systems - Heather F. Sahli; Jeffrey K. Conner (Oecologia, 2006)

Variations in virulence and genome of Mycosphaerella pinodes isolates from field peas in central Alberta, Canada - H. Su; S. F. Hwang; K. F. Chang; R. L. Conner; R. J. Howard; G. D. Turnbull (Journal of Plant Diseases and Protection, 2006)

Geographic patterns in the demersal ichthyofauna of the Aleutian Islands - E. A. LOGERWELL; K. AYDIN; S. BARBEAUX; E. BROWN; M. E. CONNERS; S. LOWE; J. W. ORR; I. ORTIZ; R. REUTER; P. SPENCER (Fisheries Oceanography, 2005)
The goals of this research were to investigate geographic patterns in the Aleutian Island region's demersal ichthyofauna and to determine whether they reflected the physical and biological oceanographic patterns documented by other authors in this volume. The analyses were structured according to the level of organization: at the community level, patterns in species occurrence and community structure were investigated; at the population level, distribution and abundance were examined; at the individual level, food habits and growth were studied. There were step‐changes in species occurrence, diversity, population distribution and food habits at Samalga Pass and at sites farther west. These longitudinal trends indicated physical and biological variation along the length of the Aleutian Islands chain; however, depth‐related patterns were as common as longitudinal patterns in demersal fish distribution. In addition, high catches of patchily distributed species occurred in areas expected to be biological ‘hot spots’ because of increased productivity and prey availability. These patterns suggest linkages between demersal fish ecology and the biophysical processes described by other authors in this volume and indicate that inter‐disciplinary research is needed to elucidate the underlying mechanisms.

A first linkage map of pecan cultivars based on RAPD and AFLP markers - Sudheer R. Beedanagari; Sue K. Dove; Bruce W. Wood; Patrick J. Conner (Theoretical and Applied Genetics, 2005)

Evolution of plant resistance and tolerance to frost damage - Anurag A. Agrawal; Jeffrey K. Conner; John R. Stinchcombe (Ecology Letters, 2004)
Plant defence against any type of stress may involve resistance (traits that reduce damage) or tolerance (traits that reduce the negative fitness impacts of damage). These two strategies have been proposed as redundant evolutionary alternatives. A late‐season frost enabled us to estimate natural selection and genetic constraints on the evolution of frost resistance and tolerance in a wild plant species. We employed a genetic selection analysis (which is unbiased by environmental correlations between traits and fitness) on 75 paternal half‐sibling families of annual wild radish [ Raphanus raphanistrum (Brassicaceae)]. In an experimental population in southern Ontario, we found strong selection favouring plant resistance to frost, but selection against tolerance to frost. The selection against tolerance may have been caused by a cost of tolerance, as we provide evidence for a negative genetic correlation between tolerance and fitness in the absence of frost damage. Although we found no evidence for the theoretically predicted trade‐off between frost tolerance and resistance among our families, we did detect negative correlational selection acting on the two traits, indicating that natural selection favoured high resistance combined with low tolerance and low resistance coupled with high tolerance, but not high or low levels of both traits together. There were few genetic correlations between the measured traits overall, but frost tolerance was negatively correlated with initial seed mass, and frost resistance was positively correlated with resistance to insect herbivory. Periodic episodes of strong selection such as that caused by the late‐season frost may be disproportionately important in evolution, and are likely becoming more common because of human alterations of the environment.

Differences in the growth stages of Erysiphe pisi on cultivars of field pea (Pisum sativum L.) - H. Su; S. F. Hwang; K. F. Chang; R. L. Conner; R. J. Howard; G. D. Turbull; S. F. Blade (Journal of Plant Diseases and Protection, 2004)

Species specificity and interspecies relatedness of NSP4 genetic groups by comparative NSP4 sequence analyses of animal rotaviruses - M. Ciarlet; F. Liprandi; M. E. Conner; M. K. Estes (Archives of Virology, 2000)

Survival and Growth of Seedlings of Four Bottomland Oak Species in Response to Increases in Flooding and Salinity - William H. Conner; Kenneth W. McLeod; James K. McCarron (Forest Science, 1998)
Four oak species representing a range of flood tolerance were chronically (simulating sea level rise) and acutely (simulating hurricane storm surge) exposed to increased flooding and salinity in a complete factorial experiment. Survival, growth, and final biomass were measured to assess differential species' responses. No Nuttall or overcup oak seedlings died when flooded with fresh water, but 10% of the swamp chestnut and 35% of the water oaks died. Floodwater salinities of 2 and 6 g L-1 resulted in mortality of all seedlings of all four species. Watering with 2 g L-1 saline water did not cause any mortality although leaf browning was evident in all species. Overcup oak seedlings were the most tolerant to watering with 6 g L-1 saline water (100% survival), while the other three species had high mortality. Increased salinity, both in watered and flooded conditions, generally resulted in decreased diameter growth and decreased root and shoot biomass. Short-term increases in salinity (simulated storm surge) resulted in total mortality of flooded seedlings, while drained seedlings recovered and leafed out the following spring. Results indicate that these bottomland oak species would be seriously affected by increased flooding and salinity from either hurricane storm surges or sea level rise. For. Sci. 44(4):618-624.

Flood and salinity stress of wetland woody species, buttonbush (Cephalanthus occidentalis) and swamp tupelo (Nyssa sylvatica var.biflora) - James K. McCarron; Kenneth W. McLeod; William H. Conner (Wetlands, 1998)

Molecular-marker analysis of quantitative traits for growth and development in juvenile apple trees - P. J. Conner; S. K. Brown; N. F. Weeden (Theoretical and Applied Genetics, 1998)

Determination of the duration of a primary immune response and the ID50 of ALA rabbit rotavirus in rabbits - M. E. Conner; D. Y. Graham; M. K. Estes (Archives of Virology, 1997)

A garden study of the effects of ultraviolet-B radiation on pollination success and lifetime female fitness in Brassica - Jeffrey K. Conner; Laura A. Zangori (Oecologia, 1997)

Comparative amino acid sequence analysis of the outer capsid protein VP4 from four lapine rotavirus strains reveals identity with genotype P[14] human rotaviruses - M. Ciarlet; M. K. Estes; M. E. Conner (Archives of Virology, 1997)

Molecular characterization of three rabbit rotavirus strains - T. N. Tanaka; M. E. Conner; D. Y. Graham; M. K. Estes (Archives of Virology, 1988)

Precopulatory sexual interaction in an arctiid moth (Utetheisa ornatrix): Role of a pheromone derived from dietary alkaloids - William E. Conner; Thomas Eisner; Robert K. Vander Meer; Angel Guerrero; Jerrold Meinwald (Behavioral Ecology and Sociobiology, 1981)

Sex attractant of an arctiid moth (Utetheisa ornatrix): A pulsed chemical signal - William E. Conner; Thomas Eisner; Robert K. Vander Meer; Angel Guerrero; Dario Ghiringelli; Jerrold Meinwald (Behavioral Ecology and Sociobiology, 1980)